2b+1=b+7

Simple and best practice solution for 2b+1=b+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2b+1=b+7 equation:


Simplifying
2b + 1 = b + 7

Reorder the terms:
1 + 2b = b + 7

Reorder the terms:
1 + 2b = 7 + b

Solving
1 + 2b = 7 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
1 + 2b + -1b = 7 + b + -1b

Combine like terms: 2b + -1b = 1b
1 + 1b = 7 + b + -1b

Combine like terms: b + -1b = 0
1 + 1b = 7 + 0
1 + 1b = 7

Add '-1' to each side of the equation.
1 + -1 + 1b = 7 + -1

Combine like terms: 1 + -1 = 0
0 + 1b = 7 + -1
1b = 7 + -1

Combine like terms: 7 + -1 = 6
1b = 6

Divide each side by '1'.
b = 6

Simplifying
b = 6

See similar equations:

| y=240+5x | | 3p+21=-6 | | y+140=5x-100 | | 4y-9=43 | | 3y=x-20 | | 5w+3w+4x+5x+10+5=c | | -5x^2+15x+1.7=0 | | x^2+4y^2-2x-24y+21=0 | | 2x^2+20x=-10 | | 12x^7+6x^4-30x^2=0 | | 2(1-y)=8m | | 2X-X-7=-1 | | 7z-3=25 | | 5(2f+3)=6f-15 | | -2(3x-5)=22 | | y=.28-.6x+1.3x-2.9 | | x^2-15x+(56.25)=74.25 | | 8X-2X-5=3+12 | | 93+8=101+93 | | 9x^2+48x+45=0 | | -2(4m-3)=4m | | 9y^2-x^2+4x+18y+5=0 | | 3n+11=-5-n | | (y+2)(y^2-2y+4)= | | 10X+2=-7 | | 9x-5=10+6x | | x+(29+x)+(-13+3*2)=634 | | -100tan^2x+25=0 | | 10sin^2(2x)=5 | | 9-4y=37 | | 3r+r+25-6=11+2-7 | | 3X+2=-7X-7 |

Equations solver categories